Nd steel enamelware, its processing method and application

CN122879703APending Publication Date: 2026-10-09ANHUI TONGHUI QINGNENG ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610949210.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]本发明的目的是为了解决现有技术中,ND钢搪瓷制品容易出现密着不良、针孔、气泡甚至鳞爆的问题,提供一种ND钢搪瓷制品的加工方法,通过本发明提供的加工方法能够确保ND钢搪瓷制品的产品质量

Benefits of technology

[0018]与现有技术相比,通过本发明提供的加工方法加工得到的ND钢搪瓷制品,搪瓷层与ND钢基体之间的密着性能优异,搪瓷层无针孔、气泡和鳞爆缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of enamel, and discloses an ND steel enamel product and a processing method and application thereof, the processing method comprises the following steps: carrying out tempering treatment on an ND steel product; naturally cooling the ND steel product after the tempering treatment; applying enamel glaze on the surface of the ND steel product after the natural cooling; and carrying out sintering treatment on the ND steel product with the applied enamel glaze, so that the enamel glaze forms an enamel layer on the surface of the ND steel product; compared with the prior art, the ND steel enamel product processed by the processing method has excellent adhesion between the enamel layer and the ND steel base body, and the enamel layer is free of pinhole, bubble and scale explosion defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of enamel technology, specifically to an ND steel enamel product, its processing method, and its application. Background Technology

[0002] ND steel (09CrCuSb) is a widely used steel for resisting sulfuric acid dew point corrosion in flue gas heat exchangers, low-temperature economizers, and chimney linings. Enameling it further enhances its resistance to low-temperature dew point corrosion, erosion, and dust accumulation, building upon its existing acid resistance. However, traditional enamel processes often result in poor adhesion, pinholes, bubbles, and even blistering on the surface of ND steel enamel products, affecting their usability. Summary of the Invention

[0003] The purpose of this invention is to solve the problems of poor adhesion, pinholes, bubbles, and even blistering in ND steel enamel products in the prior art, and to provide a processing method for ND steel enamel products. The processing method provided by this invention can ensure the product quality of ND steel enamel products.

[0004] To achieve the above objectives, the present invention provides a method for processing ND steel enamel products, comprising the following steps:

[0005] Tempering treatment is applied to ND steel products;

[0006] The tempered ND steel products are allowed to cool naturally.

[0007] Apply enamel glaze to the surface of ND steel products after they have cooled naturally;

[0008] ND steel products coated with enamel glaze are sintered to form an enamel layer on the surface of the ND steel products.

[0009] Preferably, the tempering treatment temperature is 500-700℃, and the holding time is 1-5 minutes.

[0010] Preferably, the tempering treatment temperature is 550-650℃, and the holding time is 2-4 minutes.

[0011] Preferably, the tempering process is carried out under a protective atmosphere or vacuum conditions.

[0012] Preferably, before applying the enamel glaze, the process further includes a cleaning step on the surface of the ND steel product, the cleaning process including degreasing and / or sandblasting.

[0013] Preferably, the enamel glaze includes a base glaze, and the application method is selected from one of spraying, dipping, or brushing.

[0014] Preferably, the sintering temperature of the sintering treatment is 750-850℃, and the holding time is 3-10 minutes.

[0015] Preferably, the sintering temperature of the sintering treatment is 780-800℃, and the holding time is 5-8 minutes.

[0016] The present invention also provides an ND steel enamel product processed according to the above processing method.

[0017] The present invention also provides an application of the above-described ND steel enamel product in the preparation of equipment resistant to sulfuric acid dew point corrosion.

[0018] Compared with the prior art, the ND steel enamel products processed by the processing method provided by the present invention have excellent adhesion between the enamel layer and the ND steel substrate, and the enamel layer is free of pinholes, bubbles and blistering defects.

[0019] Other features and advantages of the present invention will be described in detail in the following specific embodiments. Detailed Implementation

[0020] To make the technical means, creative features, objectives, and effects of this invention readily understandable, the invention is further illustrated below with reference to specific embodiments. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the invention.

[0021] As mentioned above, this invention provides a processing method for ND steel enamel products, including the following steps: tempering the ND steel product; naturally cooling the tempered ND steel product; applying enamel glaze to the surface of the naturally cooled ND steel product; and sintering the ND steel product coated with enamel glaze to form an enamel layer on the surface of the ND steel product.

[0022] The inventors of this application have discovered through long-term research that one of the fundamental reasons for surface quality problems such as poor adhesion of the enamel layer on ND steel lies in the hydrogen element in the ND steel matrix. During the smelting and processing of ND steel, a certain amount of hydrogen is absorbed, which exists in a solid solution or trapped state within the ND steel matrix. During the high-temperature sintering process of traditional enamel technology, hydrogen atoms in the ND steel matrix gain sufficient kinetic energy to diffuse to the surface of the ND steel matrix and accumulate at the interface between the enamel layer and the ND steel matrix, forming hydrogen molecules and generating extremely high internal pressure, leading to surface quality problems such as poor adhesion of the enamel layer.

[0023] According to the technical solution provided by the present invention, by tempering the ND steel before enamel sintering, the hydrogen element in the ND steel matrix obtains sufficient diffusion kinetic energy at high temperature and escapes rapidly from the ND steel matrix. The hydrogen content in the ND steel matrix after tempering is greatly reduced, and there is no longer sufficient hydrogen release during the subsequent enamel sintering process, which fundamentally eliminates surface quality problems such as poor adhesion.

[0024] It should be noted that the tempering treatment described in this invention differs from traditional long-time tempering. This invention does not aim to alter the microstructure of the ND steel matrix, but rather focuses on dehydrogenation. The ND steel has already undergone complete heat treatment before leaving the factory, and its microstructure is already in a stable state. This invention applies a short-duration high-temperature tempering treatment, utilizing the high diffusion coefficient of hydrogen in α-Fe within a certain temperature range, to significantly reduce the hydrogen content in the surface and near-surface regions of the ND steel matrix. This avoids surface quality problems caused by hydrogen escaping during enamel sintering. In some embodiments, the tempering temperature is 500-700℃, and the holding time is 1-5 minutes. More preferably, the tempering temperature is 550-650℃, and the holding time is 2-4 minutes.

[0025] It is understood that the short-time high-temperature tempering process adopted in this invention can not only effectively overcome surface quality problems such as poor adhesion in traditional enamel processes, but also avoid the problems of coarsening of the ND steel matrix and deterioration of mechanical properties that may be caused by long-time high-temperature tempering, thus maintaining the original sulfuric acid dew point corrosion resistance of ND steel. Furthermore, this invention adopts a short-time high-temperature tempering process, which only requires adding a short-time high-temperature tempering process to the existing enamel process, and has good compatibility with existing enamel production lines. The tempering time is only 1-5 minutes, which can be seamlessly connected with the enamel glazing and sintering processes to form a continuous production line, thus making it suitable for large-scale industrial production applications, with significant economic benefits and application prospects.

[0026] In this embodiment of the invention, the tempering treatment can be performed using a continuous heat treatment furnace or a roller furnace. In specific operation, the ND steel product is fed into the furnace, and the furnace temperature is increased to the target temperature at a heating rate of 10-30℃ / min. Once the surface temperature of the ND steel product is consistent with the furnace temperature, the holding time is started.

[0027] In some embodiments, the tempering treatment is performed under a protective atmosphere or vacuum. It is understood that tempering under a protective atmosphere or vacuum effectively prevents excessive oxidation of the surface of ND steel products at high temperatures. Specifically, the protective atmosphere may be nitrogen or argon.

[0028] In some embodiments, before applying the enamel enamel, a cleaning step is included on the surface of the ND steel product. This cleaning removes oil, dust, and oxide layers from the ND steel product surface, ensuring good contact and wetting between the enamel enamel and the ND steel substrate. Specifically, the cleaning includes degreasing and / or sandblasting. Degreasing can be performed using alkaline washing, electrochemical degreasing, or organic solvent cleaning to remove residual grease and contaminants from the ND steel product surface during processing. Sandblasting can use quartz sand, corundum, or steel grit as abrasive, with a sandblasting pressure of 0.4-0.8 MPa. After sandblasting, the surface roughness Ra of the ND steel product is controlled at 1.6-4.0 μm to obtain a suitable surface morphology for enamel enamel adhesion. After cleaning, enamel enamel application is preferably performed within 4 hours to prevent re-oxidation or impurity adsorption on the ND steel product surface.

[0029] In some embodiments, the enamel glaze includes a base glaze, and the application method is selected from one of spraying, dipping, or brushing.

[0030] In this embodiment of the invention, the enamel glaze may consist only of a base glaze, which is applied to the surface of the ND steel substrate. During sintering, the base glaze undergoes an oxidation-reduction reaction with the ND steel substrate, forming a chemical bond and mechanical anchoring. The base glaze can be a conventional enamel base glaze formulation in the art, such as a silicate-based glaze containing cobalt, nickel, manganese, and other adhesion oxides. Before application, the base glaze is mixed with water or an organic solvent in a specific ratio and ball-milled to a specific gravity of 1.60-1.80 g / cm³. 3 Glaze.

[0031] When applying the coating, those skilled in the art can adapt to the specific structural form of the ND steel product and choose any one of the following methods: spraying, dipping, or brushing.

[0032] For example, for ND steel products with complex structures, internal cavities, or tubular shapes, such as ND steel heat exchange tubes, economizer tubes, or condenser tube bundles, dip coating is preferred. During dip coating, the entire ND steel product is immersed in a container filled with glaze slurry, ensuring the slurry fully wets and covers the inner and outer surfaces and corners of the product. After standing for 10-30 seconds, the product is slowly pulled out of the liquid at a uniform speed of 5-15 cm / min, and the product is rotated to allow excess glaze slurry to flow naturally, ensuring a uniform glaze coating without any dead corners.

[0033] For ND steel products with large areas and relatively simple shapes, such as flat plates or the outer walls of large tanks, spraying is the preferred method for coating. During spraying, the spraying pressure should be controlled at 0.2-0.5MPa, the spraying distance should be 150-300mm, and the spray gun should be kept perpendicular to the surface of the product and moved at a uniform speed to form a uniform glaze coating and avoid localized excessive thickness or sagging.

[0034] For local repairs or small-batch trial production of products, this invention can also be applied by brushing. Specifically, when brushing, a soft-bristled brush is used to dip into the glaze paste and apply it evenly to the surface of the ND steel product. During the brushing process, unidirectional, thin-coat, and multi-layer operations should be performed to ensure the uniformity and adhesion of the coating.

[0035] It should be noted that, regardless of which coating method is used, after coating, the glazed ND steel product should be left to stand at room temperature for 5-15 minutes to level, or placed in a drying oven at 80-120℃ for 5-10 minutes to allow the moisture or solvent in the glaze to fully evaporate, thus avoiding pinholes or bubbles in the enamel layer due to rapid vaporization of moisture during the subsequent sintering process.

[0036] It is understood that, in some embodiments of the present invention, the enamel glaze may further include a top glaze, that is, a top glaze is applied on top of the base glaze layer. The top glaze is used to impart a smooth and beautiful surface to the enamel product, as well as physical and chemical properties such as acid resistance and wear resistance. In the embodiments of the present invention, the top glaze may be selected from those known in the art, such as titanium top glaze, antimony top glaze, etc.

[0037] In some embodiments, the sintering temperature of the sintering treatment is 750-850°C, and the holding time is 3-10 minutes; more preferably, the sintering temperature of the sintering treatment is 780-800°C, and the holding time is 5-8 minutes.

[0038] In this embodiment of the invention, the purpose of the sintering treatment is to melt and level the enamel glaze at high temperature, and to form a chemical bond with the ND steel substrate through an oxidation-reduction reaction, thereby obtaining a dense, smooth enamel layer that is firmly bonded to the ND steel substrate.

[0039] More specifically, in some embodiments of the present invention, during the specific sintering process, the furnace temperature can be set to rise to the target temperature at a heating rate of 15-25℃ / min, and then held at the target temperature before naturally cooling to room temperature. After sintering is completed, the thickness of the enamel layer is 100-200μm.

[0040] In this embodiment of the invention, the sintering process is preferably carried out in an air atmosphere, which facilitates the oxidation-reduction reaction between the enamel glaze and the ND steel substrate at a lower cost.

[0041] This invention also provides an ND steel enamel product processed according to the above processing method. The adhesion level between the enamel layer and the ND steel substrate of the ND steel enamel product can reach level 1 or above, and the enamel layer has no surface quality problems such as poor adhesion.

[0042] This invention also provides an application of the above-mentioned ND steel enamel product in the preparation of equipment resistant to sulfuric acid dew point corrosion. Specifically, the ND steel enamel product can be used as or processed into components in equipment such as boiler air preheaters, economizers, heat exchangers, condensers, flue pipes, and chimney linings. In these applications, the ND steel enamel product utilizes the inherent sulfuric acid dew point corrosion resistance of the ND steel substrate, and further enhances corrosion resistance, wear resistance, and dust accumulation resistance through the surface enamel layer, significantly extending the service life of the equipment in low-temperature sulfuric acid-containing environments.

[0043] The following specific embodiments further illustrate the processing method of ND steel enamel products provided by the present invention.

[0044] The ND steel enamel products provided in this embodiment of the invention are tested for various properties using the following method.

[0045] 1. Enamel layer adhesion performance:

[0046] An impact hammer test was conducted on the enamel-coated product. The impact hammer had a mass of 1.5 kg, was hemispherical, and had a diameter of 22 mm. The diameter of the circular hole on the impact base was 20.6 mm, and the impact radius was 2 mm.

[0047] Clean the surface of the enamel-coated product, then fix it between the base and support frame of the impact test bench. Place the impact hammer at a height of 500mm and impact the surface of the enamel-coated product. After the porcelain cracking phenomenon after the impact has completely stopped, evaluate the adhesion strength grade of the enamel layer of the enamel-coated product. The grade evaluation criteria are as follows:

[0048] Level 1: The surface after impact is completely covered with enamel and has a glossy appearance (best adhesion strength).

[0049] Level 2: The surface after impact is almost completely covered with enamel.

[0050] Level 3: After impact, most of the enamel layer remains, with a small amount of exposed iron (relatively good).

[0051] Level 4: After impact, a small portion of the enamel layer remains, with a large amount of exposed iron (relatively poor).

[0052] Level 5: After impact, all enamel is detached, and the enamel layer and metal substrate are separated very clearly (very poor).

[0053] 2. Surface defects:

[0054] Under natural light, at a distance of 50cm from the sample, a comprehensive visual inspection is conducted on the surface of the enamel product to check for defects such as flaking (fish-scale-like peeling), pinholes (holes less than 1mm in diameter), and bubbles (surface protrusions or pits formed after bursting). The quantity and distribution of each type of defect are recorded.

[0055] 3. Thermal shock resistance:

[0056] The enamel product is heated to 250℃ and kept at that temperature for ten minutes. Then it is quickly immersed in water at 20±5℃ to cool. After repeating the thermal shock cycle five times, the surface of the enamel product is thoroughly inspected by visual inspection to observe whether there are cracks or peeling defects in the enamel layer.

[0057] 4. Corrosion resistance:

[0058] Enameled products were subjected to sulfuric acid corrosion tests at 20℃ and 20% H2SO4 and 70℃ and 50% H2SO4 for 24 hours respectively, and the corrosion phenomenon was observed.

[0059] Example 1

[0060] ND steel (09CrCuSb) with a thickness of 3mm was selected as the base material. The ND steel plate was placed in a continuous heat treatment furnace and tempered under a nitrogen protective atmosphere. The temperature was raised to 600℃ at a heating rate of 20℃ / min, held for 3 minutes, and then removed from the furnace and allowed to cool naturally to room temperature in the air.

[0061] The cooled ND steel plate was degreased and sandblasted. The sandblasting pressure was 0.6 MPa and the roughness Ra was controlled at 2.0-3.0 μm.

[0062] Commercially available enamel base glaze was mixed with water in a certain proportion and ball-milled to a specific gravity of 1.70 g / cm³. 3 The glaze paste was applied evenly to the surface of the ND steel plate by spraying at a pressure of 0.3 MPa and a distance of 200 mm, resulting in a coating thickness of 120 μm.

[0063] After coating, let it dry at room temperature for 10 minutes, then place it in a sintering furnace and heat it to 800°C at a rate of 20°C / min in air atmosphere. Hold it at that temperature for 6 minutes for sintering. After sintering, let it cool naturally to room temperature to obtain ND steel enamel products.

[0064] Example 2

[0065] The ND steel plate provided in Example 1 was processed in the same way as in Example 1, except that the tempering temperature was adjusted to 550°C and the holding time was adjusted to 4 minutes. The ND steel enamel products were obtained. The evaluation results of the ND steel enamel products are summarized in Table 1.

[0066] Example 3

[0067] The ND steel plate provided in Example 1 was processed in the same way as in Example 1, except that the tempering temperature was adjusted to 650°C and the holding time was adjusted to 2 minutes. The ND steel enamel products were obtained. The evaluation results of the ND steel enamel products are summarized in Table 1.

[0068] Example 4

[0069] The ND steel plate provided in Example 1 is processed in the same way as in Example 1, except that the tempering temperature is adjusted to 500°C and the holding time is adjusted to 5 minutes. The ND steel enamel products are obtained. The evaluation results of the ND steel enamel products are summarized in Table 1.

[0070] Example 5

[0071] The ND steel plate provided in Example 1 was processed in the same way as in Example 1, except that the tempering temperature was adjusted to 700°C and the holding time was adjusted to 1 minute. The ND steel enamel products were obtained. The evaluation results of the ND steel enamel products are summarized in Table 1.

[0072] Example 6

[0073] ND steel pipe (09CrCuSb) with a wall thickness of 4mm was selected as the base material. The ND steel pipe was placed in a vacuum heat treatment furnace under vacuum conditions (vacuum degree ≤ 1×10). -2 The ND steel enamel product was subjected to tempering treatment at a heating rate of 15℃ / min to 600℃, held for 3 minutes, and then removed from the furnace and allowed to cool naturally to room temperature in air. The subsequent cleaning, glazing, and sintering steps were the same as in Example 1, with a sintering temperature of 780℃ and a holding time of 7 minutes. After sintering, the product was allowed to cool naturally to room temperature to obtain the ND steel enamel product. The evaluation results of the ND steel enamel product are summarized in Table 1.

[0074] Comparative Example 1

[0075] The same ND steel plate as in Example 1 was selected as the substrate. Without tempering, it was directly degreased and sandblasted for cleaning. Then, the same enamel glaze as in Example 1 was applied, and sintering was carried out under the same sintering conditions to obtain ND steel enamel products. The evaluation results of the ND steel enamel products are summarized in Table 1.

[0076] Comparative Example 2

[0077] The same ND steel plate as in Example 1 was selected as the substrate, and conventional long-time tempering was adopted. Specifically, the ND steel plate was placed in a continuous heat treatment furnace and tempered under a nitrogen protective atmosphere. The temperature was raised to 600°C at a rate of 20°C / min and held for 60 minutes before being removed from the furnace. The remaining treatments were exactly the same as in Example 1, and ND steel enamel products were obtained. The evaluation results of the ND steel enamel products are summarized in Table 1.

[0078] Table 1: Properties of ND steel enamel products obtained from Examples 1-6 and Comparative Examples 1-2

[0079]

[0080] Based on the above experimental data, it can be seen that the processing method provided by the present invention effectively improves the adhesion performance between the ND steel substrate and the enamel layer, fundamentally eliminating surface quality problems such as poor adhesion, pinholes, bubbles, and even scale bursts.

[0081] The ND steel enamel product obtained in Comparative Example 1 had an adhesion grade of 5, indicating very poor adhesion performance. The enamel layer had pinholes, bubbles, and blistering defects, and after thermal shock testing, obvious cracks and a small amount of obvious enamel peeling appeared. Furthermore, due to surface quality issues, slight corrosion occurred after corrosion resistance testing.

[0082] In Comparative Example 2, after high-temperature tempering, the enamel layer was effectively adhered to the surface of ND steel, i.e., the adhesion performance was good. However, further comparative tests on mechanical impact resistance revealed that the impact resistance of Comparative Example 2 was significantly weaker than that of the ND steel enamel product in Example 1.

[0083] The foregoing has shown and described the basic principles, main features, and characteristics of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A method for processing ND steel enamel products, characterized in that, Includes the following steps: Tempering treatment is applied to ND steel products; The tempered ND steel products are allowed to cool naturally. Apply enamel glaze to the surface of ND steel products after they have cooled naturally; ND steel products coated with enamel glaze are sintered to form an enamel layer on the surface of the ND steel products.

2. The processing method according to claim 1, characterized in that, The tempering treatment is performed at a temperature of 500-700℃ for 1-5 minutes.

3. The processing method according to claim 2, characterized in that, The tempering treatment is performed at a temperature of 550-650℃ for 2-4 minutes.

4. The processing method according to any one of claims 1-3, characterized in that, The tempering process is carried out under a protective atmosphere or vacuum.

5. The processing method according to claim 1, characterized in that, Before applying the enamel glaze, the process includes a cleaning step on the surface of the ND steel product, which includes degreasing and / or sandblasting.

6. The processing method according to claim 1, characterized in that, The enamel glaze includes a base glaze, and the application method is selected from one of spraying, dipping, or brushing.

7. The processing method according to claim 1, characterized in that, The sintering temperature for the sintering treatment is 750-850℃, and the holding time is 3-10 minutes.

8. The processing method according to claim 7, characterized in that, The sintering temperature for the sintering treatment is 780-800℃, and the holding time is 5-8 minutes.

9. ND steel enamel products processed by the processing method according to any one of claims 1-8.

10. The application of the ND steel enamel product as described in claim 9 in the preparation of equipment resistant to sulfuric acid dew point corrosion.